Energy and protein intake and its association with malnutrition risk among community-living older adults in Kuantan, Pahang - Sheikh Hishamuddin, Siti Nur Amirah; Mohammad Rosli, Nur Izzati; Hamirudin, Aliza Haslinda (IIUM Press, 2025)
Background: Inadequate dietary intake among older adults poses a public health concern as it could lead to adverse effects, including malnutrition risk and poor health outcomes. Thus, this study aimed to assess the energy and protein intake of community living older adults in Kuantan, Pahang, and its association with malnutrition risk. Another objective was to identify sources of protein foods commonly consumed in this studied population. Methods: A cross-sectional study was conducted among community-living older adults in Kuantan, Pahang. The dietary intake data were obtained from the diet history method. Malnutrition risk was assessed using Mini Nutritional Assessment-Short Form (MNA-SF). Anthropometric measurements of weight and height were performed for body mass index (BMI) calculation. Data was analysed using descriptive statistics, one-sample t-test, and one-way ANOVA. P-value was set at p<0.05 as statistically significant. Results: A total of seventy-three (n=73) community living older adults participated in this study, with a mean age of 65.88±5.67 years, and a mean BMI was 26.023±4.21 kg/m2. Findings showed that energy and protein intake of the respondents were significantly lower than the Recommended Nutrient Intake (RNI). The most common protein sources consumed by the respondents were animal-based sources, particularly fish (80.8%). Eating at home was more practiced by respondents than eating out. Advancing age was significantly associated with malnutrition risk. No significant differences between MNA-SF categories with energy and protein intake were identified. Conclusion: Energy and protein intake were inadequate among older adults in this present study. Malnutrition risk was prevalent in this population, with older age groups being significantly at risk. Strategies to address nutritional issues among Malaysian community older adults are warranted for optimum nutritional and health status.